On the number of nodal domains on a rectangle with a slit - Kerner, J. (Methods of Functional Analysis and Topology, 2021)
In spectral geometry, one is interested in estimating the number of nodal domains of eigenfunctions of the Laplacian on planar domains. Well-known classical results due to Courant and Pleijel establish upper bounds, implying that the n-th eigenfunction has at most n nodal domains and that indeed only a finite number of eigenfunctions attain this maximal value. Surprisingly, however, a seemingly simpler question remains largely open. Namely, does there always exist a subsequence of eigenfunctions with an unbounded number of nodal domains? It is the aim of this note to investigate this question in the context of a rectangular domain with a slit. В спектральній геометрії цікавим є оцінка кількості вузловіих областей власних функцій лапласіана в плоских областях. Відомі класичні результати Куранта і Плейеля встановлюють верхні межі, з яких випливає, що n-та власна функція має не більше ніж n вузлових областей, і лише скінченна кількість власних функцій досягають цього максимального значення. Однак, більш просте питання ще залишається відкритим. А саме, чи завжди існує підпослідовність власних функцій з необмеженою кількість вузлових областей? Метою цієї роботи є дослідження цього питання в контексті прямокутної області з прорізом.